Green Purchasing And Environmental Performance: The Moderating Effect Of Top Management Support In Greater Accra Metropolitan Assembly - Zakaria, Yussif (KNUST, 2023)
A thesis submitted to the department of supply chain and information systems, institute of distance learning, in partial fulfillment of the requirements for the degree of master of science (procurement and supply chain management option)